2009
DOI: 10.4012/dmj.28.461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness on initial responses of osteoblast-like cells on two types of zirconia

Abstract: The aim of this study was to evaluate the effect of surface roughness on the initial attachment of mouse osteoblast-like cells on ceria stabilized zirconia/alumina nanocomposite (NANOZR) and yttria-stabilized zirconia (3Y-TZP) in comparison to those on pure titanium (Ti) and alumina oxide (AO). Specimens with smooth and rough surfaces were prepared by grinding with diamond paper or by sandblasting, respectively. For four substrates examined, the number of attached cells on the rough surface specimens was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 36 publications
9
90
4
Order By: Relevance
“…In contrast, Yamashita et al have studied attachment of osteoblast-like cells on 2 kinds of ceramics and reported that surface condition had no effect on initial attachment because the specimen surface was covered by chemically stable oxide [43]. Price et al have made composites of ceramics and carbon nanofibers and reported that the finer surface of the specimens increased the attachment area of osteoblasts, and the number of attached cells increased with an increase in the addition of carbon nanofibers [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Yamashita et al have studied attachment of osteoblast-like cells on 2 kinds of ceramics and reported that surface condition had no effect on initial attachment because the specimen surface was covered by chemically stable oxide [43]. Price et al have made composites of ceramics and carbon nanofibers and reported that the finer surface of the specimens increased the attachment area of osteoblasts, and the number of attached cells increased with an increase in the addition of carbon nanofibers [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it was shown that by introducing surface roughness in 3Y-TZP, the cell response was similar to titanium and alumina, concluding that roughened zirconia surface represents an appropriate substrate for proliferation and spreading of osteoblastic cells (Bächle et al, 2007;Wenz et al, 2008;Yamashita et al, 2009). It was also reported that zirconia dental implants with acid etched surface (CeraRoot implants with 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 ICE™ surface) showed a similar or higher success rate as for Titanium implants after 5 years of follow-up study (Oliva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have described the early stages of osteoblast-zirconia attachment, proliferation, differentiation and activity [10][11][12] . The initial attachment of fibroblasts, assuming soft tissue adhesion, on zirconia or Ti discs has also been investigated 13,14) , and these studies have confirmed the similar biological responses of each type of cell on each material.…”
Section: Introductionmentioning
confidence: 99%